Effect of message framing on improving oral health behaviors in students in Qazvin, Iran - Amir Pakpour Haji Agha; Saeedeh Nourozi; Mir Saeed Yekaninejad; Asieh Mansouri; Samira Chaibakhsh (Isfahan University of Medical Sciences, 2013)
AbstractIntroduction: This study was undertaken to compare the effect of two loss-oriented and gain-oriented messages on improving attitude, intention and oral health-related behaviors among students in Qazvin, Iran.Materials and Methods: In this randomized controlled trial the subjects were selected by stratified cluster sampling. The participants were asked to complete a questionnaire containing questions on attitude towards toothbrushing and flossing, intention to brush and floss and self-reported frequencies of toothbrushing and flossing behaviors during a week. The subjects were then assigned randomly to gain-oriented (n = 60) or loss-oriented (n = 60) groups and accordingly received pamphlets on the benefits of toothbrushing and flossing and and consequences of not brushing and flossing. The participants were asked to complete the questionnaire again one week after the intervention. Simultaneously, a checklist was completed on oral health behavior. Data were analyzed with ANCOVA and repeated measures ANOVA using SPSS.Results: ANCOVA revealed that participants who were exposed to loss-oriented messages exhibited more favorable attitudes and intentions than those who were exposed to gain-oriented messages (p value < 0.001). Furthermore, the repeated measures ANOVA indicated that students in the loss-oriented group reported higher frequencies of toothbrushing and flossing behaviors (p value < 0.001).Conclusion: The study showed that loss-oriented messages should not be ignored. It appears that the loss-oriented messages are more compatible with the collective culture and they result in the promotion of oral health among students and adolescents. Key words: Behavior, Oral health, Students